The Urgency of Learning Indonesian based on Local Wisdom - Agita Misriani; Shesilia Cintari; Nuriza Zulyani (International Journal of Social Service and Research (IJSSR), 2023)
The purpose of writing this article is to describe the relevance or usefulness of learning Indonesian based on local wisdom in order to lead students with character in the life of the nation and state. The method used is qualitative with a literature study approach on learning Indonesian and local wisdom. Indonesian is the national language or state language. The competency standard for Indonesian language subjects is oriented towards the nature of language learning, that learning a language is learning to communicate and learning literature is learning to respect humans and their human values. Indonesian language learning is directed at increasing students' ability to communicate in Indonesian, both orally and in writing as well as creating respect for human creations. Through learning Indonesian, students are expected to become individuals who can appreciate and be proud of using the Indonesian language. Besides that, learning Indonesian also has a very important role in maintaining culture and customs in Indonesia. Learning Indonesian based on local wisdom is an effective way to preserve the existence of local culture through integrated learning at schools.